Synthesis of Structure and Function Diverse α-D-Diazoacetates, α-D-Diazoacetamides, α-D-Diazoketones, and the Antibiotic α-D-Azaserine - Bew, Sean P.; Ashford, Polly-Anna; Bachera, Dominika U. (Synthesis, 2013)
Using 0.1 mol% to 1 mol% potassium carbonate in an acetonitrile–deuterium oxide mixture acts as a ‘privileged’ reaction system, which at ambient temperature affords, via a one-pot–one-cycle procedure, α-D-diazoacetates, α-D-diazoacetamides, or α-D-diazoketones from the corresponding nondeuterated form. The protocol is inexpensive, employs readily available materials, does not require harsh reaction conditions, requires two hours for completion, and affords the desired products in good yields and with excellent levels of deuterium incorporation. Exemplifying our protocol the first isotope labelled synthesis of N-Boc-α-D-azaserine with ≥95% D-incorporation is reported.
Keywords: isotope; deuterium-labelled compounds; diazoester; azaserine